If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-9x + 2) = -1x + -34 Reorder the terms: -3(2 + -9x) = -1x + -34 (2 * -3 + -9x * -3) = -1x + -34 (-6 + 27x) = -1x + -34 Reorder the terms: -6 + 27x = -34 + -1x Solving -6 + 27x = -34 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -6 + 27x + x = -34 + -1x + x Combine like terms: 27x + x = 28x -6 + 28x = -34 + -1x + x Combine like terms: -1x + x = 0 -6 + 28x = -34 + 0 -6 + 28x = -34 Add '6' to each side of the equation. -6 + 6 + 28x = -34 + 6 Combine like terms: -6 + 6 = 0 0 + 28x = -34 + 6 28x = -34 + 6 Combine like terms: -34 + 6 = -28 28x = -28 Divide each side by '28'. x = -1 Simplifying x = -1
| 6sin(6x)= | | 14x=3-(-11) | | 3x+9=x-5 | | 21x-5=14 | | 9w^3-4w=0 | | 7+2(x-3)=-9 | | 12-45=3(x-2)-3 | | 5(-5y+-4)=-13y+-32 | | 7+3(x-3)=-9 | | y-16=5y | | (-4)(9)-(-5)(4)= | | 5(-5y+-4)=-13y+32 | | 3(7y-4)=9y | | x^2+21x-72=0 | | 5x+6=3+7x-9 | | 2x^2-x=-1 | | 2(x-1)-3x=16-3(x+2) | | 5t^2+38t+48=0 | | 2x+4(3x+8)= | | -5(3x+5)=-10x+20 | | 12c^2=45+51c | | (11r+5)(6r-7)=0 | | 3(x-a)+2(x+a)=a | | 8(4x-3)=64 | | 3x+19=4x+7 | | x+1=y+10 | | 4.1x-5.4-5.7x=-0.6x-5.4 | | 27-112= | | 10x+7=x+97 | | 2x-5x+6=-64 | | -5(3x+5)=-13y+-32 | | 8*14= |